A low cost seasonal solar soil heat storage system for greenhouse heating: Design and pilot study. (15th October 2015) - Zhang, Liang; Xu, Peng; Mao, Jiachen; Tang, Xu; Li, Zhengwei; Shi, Jianguo
Highlights: A low cost seasonal solar soil heat storage system used in greenhouse is invented. Establish TRNSYS model of heat collection & storage with calibration of actual data. Use EnergyPlus to calculate energy saving compared with conventional solar system. Use TRNSYS model to further modify the system by optimizing key system parameters. Pilot study is conducted and SSSSHS system proves to be energy efficient in Shanghai. Abstract: A low cost Seasonal Solar Soil Heat Storage (SSSHS) system used for greenhouse heating was invented and investigated. With soil heat storage technology, the solar energy stored in soil under greenhouse can be utilized to reduce the energy demand of extreme cold and consecutive overcast weather in winter. Unlike conventional underground heat systems, heat pumps are not needed in this system and so the cost is drastically reduced. After the tests, the system proved that seasonal thermal energy storage (STES) is feasible and can partially solve the solar heat demand and supply imbalance problem between summer and winter. TRNSYS is used to simulate the process and effect of solar energy collection and soil heat storage, and the model is calibrated by operational data in a full season. Energy consumption of the SSSHS system and conventional solar heating system have been compared under the same condition: when the indoor air temperature of the greenhouse is kept above 12 °C throughout the year, the energy saving in Shanghai was 27.8 kW h/(m 2 typical greenhouse area ⋅ year). In the end, the paper discusses the system optimization, including the optimized solar collector area and depth of buried U-pipes, and the results of a pilot test.